Perkembangan cerpen Melayu: Dari cerita moyang ke Dewan Sastera - A.Wahab Ali, (Universiti Kebangsaan Malaysia, 2009)
This article reviews the development of Malay short stories from its beginning to its glorous period with the estasblishment of the magazine Dewan Sastera in 1985. Included in the critical review are concept of Malay short story, changes in Malay society, factors leading to the emergence and characteristics of the short stories, factors leading to its development and important figures contributing their works